2002
DOI: 10.1016/s0736-0266(01)00180-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of p105 protein in NFκB activation in ANA‐1 murine macrophages following stimulation with titanium particles

Abstract: Macrophage activation by particulate debris from orthopaedic implants triggers an inflammatory response that ultimately leads to periprosthetic bone resorption and implant failure. TNFa has been identified as a critical cytokine involved in the response to debris particles but the mechanisms involved in activation of TNFx synthesis are unclear. The current study demonstrates rapid induction of T N F r following stimulation with titanium particles in the murine macrophage cell line, ANA-1, Electrophoretic mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…They showed that titanium particles activate mitogen-activated protein kinase, and pharmacological inhibition of tyrosine and serinekhreonine kinaseactivity inhibited particle-induced NF-kB activation. Soloviev et al [32] have investigated titanium particle-induced NF-kB activation in ANA-I murine macrophages. In these cells particles activate NF-kB and the activated NF-kB complexes contain the p50, p65 and c-re1 subunits.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that titanium particles activate mitogen-activated protein kinase, and pharmacological inhibition of tyrosine and serinekhreonine kinaseactivity inhibited particle-induced NF-kB activation. Soloviev et al [32] have investigated titanium particle-induced NF-kB activation in ANA-I murine macrophages. In these cells particles activate NF-kB and the activated NF-kB complexes contain the p50, p65 and c-re1 subunits.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is sequestered in the cytoplasm by an inhibitor κBα (IκBα), which binds to NF-κB and prevents its translocation to the nucleus (Chen and Ghosh 1999). TNF-α induction seems to be affected in some part of NF-κB binding to the kB2 site of the TNF-α promotor (Soloviev et al 2002). An important issue in order to find therapeutic strategies is to determine the cellular response to wear particles with different properties.…”
Section: Mechanisms Of Cell Activation In Particle Diseasementioning
confidence: 99%
“…NF-κB has been shown to be required for osteoclast development (Franzoso et al 1997). Lipopolysaccharide (LPS) appears to activate pathways other than the ones activated by particles: both agonists cause NF-κB activation, but LPS has an inhibitory effect on IκB (Soloviev et al 2002).…”
Section: Mechanisms Of Cell Activation In Particle Diseasementioning
confidence: 99%
“…Studies have also shown a variety of cell signaling pathways are involved in the cellular response to debris. These include mitogenactivated protein kinase activation [1], induction of granulocyte macrophage colony-stimulating factor [6], C-C chemokine expression [55], matrix metalloproteinase induction [56], NFkB activation [59,66,72], nitric oxide elicitation [45,64,75], induction of apoptosis [74], cytokine activation [43,78], and direct activation of cyclooxygenase-2 [82]. Although most studies on the etiology of aseptic loosening have been focused on macrophage as the central cell of interest, there is recent interest in examining the role of the fibroblasts in the MMPs 56 UHMWPE = ultrahigh-molecular-weight polyethylene; IL = interleukin; TNF = tumor necrosis factor; GM-CSF = granulocyte macrophage colony-stimulating factor; MMPs = matrix metalloproteinases.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%